Down syndrome candidate region-1 protein interacts with Tollip and positively modulates interleukin-1 receptor-mediated signaling - Lee, Jae Youn; Lee, Hyun Jung; Lee, Eun Jung; Jang, Sung Hee; Kim, Hyeyoung; Yoon, Joo-Heon; Chung, Kwang Chul (Biochimica et biophysica acta, 2009)
The Down syndrome candidate region-1 gene ( DSCR1, also known as RCAN1) is situated close to the Down Syndrome Critical Region (DSCR), which contains genes responsible for many features of Down syndrome. DSCR1 modulates calcineurin phosphatase activity, though its functional role is incompletely understood. Here we investigated the role of DSCR1-1S isoform in IL-1 receptor (IL-1R)-mediated signaling by analyzing interaction between DSCR1-1S and the IL-1R pathway components Tollip, IRAK-1, and TRAF6. Co-immunoprecipitation analyses of HEK293 cells revealed that DSCR1-1S interacted with Tollip, an IRAK-1 inhibitor, leading to the dissociation of IRAK-1 from Tollip. Similarly, both DSCR1-1S and Tollip interacted with TRAF6, with DSCR1 reducing interaction between Tollip and TRAF6. DSCR1-1S also stimulated IL-1R-mediated signaling pathways, TAK1 activation, NF-κB transactivation, and IL-8 production, all downstream consequences of IL-1R activation. Together, these results suggest that DSCR1-1S isoform positively modulates IL-1R-mediated signaling pathways by regulating Tollip/IRAK-1/TRAF6 complex formation.